Kinematic analysis in healthy and hip-dysplastic German Shepherd dogs - Miqueleto, N. S M L [UNESP]; Rahal, Sheila Canevese [UNESP]; Agostinho, F. S. [UNESP]; Siqueira, E. G M [UNESP]; Araújo, F. A P [UNESP]; El-Warrak, A. O. (Elsevier, 2013)
This study investigated kinematic patterns in clinically normal German Shepherd dogs (GSDs) compared to those with hip dysplasia and with no clinical signs of lameness. Two groups of GSDs, including 10 clinically healthy dogs (G1) and 10 with hip dysplasia (G2), were trotted on a treadmill at a constant speed. Kinematic data were collected by a 3-camera system and analysed by a motion-analysis program. Flexion and extension joint angles and angular velocities were determined for the shoulder, elbow, carpal, hip, stifle, and tarsal joints.Within each group, the differences between the right and left limbs in all kinematic variables were not significant. Minimum angle, angular displacement and minimum angular velocity did not differ between groups. Significant differences were observed in the maximum angular velocity and maximum angle of the hip joint (dysplastic. >. healthy), and in the maximum angular velocity of the carpal joint (healthy. >. dysplastic). It was concluded that, when trotting on a treadmill, dysplastic dogs with no signs of lameness may present joint kinematic alterations in the hind as well as the forelimbs. © 2012 Elsevier Ltd.
Keywords: Degenerative disease; Gait analysis; Hip; Objective measurement; Trot; angular displacement; carpal joint; dog; elbow; German Shepherd; hindlimb; hip; hip dysplasia; joint function; kinematics; limb; maximum angular velocity; minimum angle; minimum angular velocity; nonhuman; physical parameters; shoulder; tarsal joint; treadmill ergometry; Canis familiaris